DAMPAK PENERAPAN PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN - NATHALIA GOZALI (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Implementation of good corporate governance is used by companies to improve the quality of earnings by taking into account the interests of stakeholders. Good corporate governance is defined as structures, systems and processes used by the organ company to provide value-added sustainable enterprises in the long run. Benefits of implementing good corporate governance can enhance shareholder value, improve financial performance, reduce risk that may be performed by a board of commissioners with the decisions that benefit themselves and good corporate governance can increase investor confidence. The purpose of the discussion paper is to investigate the impact of the application of the principles of good corporate governance to company performance. Based on the discussions that have been done show that better good corporate governance to enhance company performance. The best the implementation of good corporate governance has links with the internal control of the company. Besides timeliness of financial reporting is a significant tool in predicting the success of a company in addition to several other financial factors. The concept of good corporate governance can produce the performance of good company.